The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.2106/jbjs.16.01002
|View full text |Cite
|
Sign up to set email alerts
|

Oral-Only Linezolid-Rifampin Is Highly Effective Compared with Other Antibiotics for Periprosthetic Joint Infection

Abstract: Background:The medical treatment of periprosthetic joint infection (PJI) involves prolonged systemic antibiotic courses, often with suboptimal clinical outcomes including increased morbidity and health-care costs. Oral and intravenous monotherapies and combination antibiotic regimens were evaluated in a mouse model of methicillin-resistant Staphylococcus aureus (MRSA) PJI.Methods:Oral linezolid with or without oral rifampin, intravenous vancomycin with oral rifampin, intravenous daptomycin or ceftaroline with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 52 publications
(49 reference statements)
0
65
0
1
Order By: Relevance
“…The most common mouse models are periprosthetic models of infection, which are employed to investigate the efficacy of different treatment modalities in a posttotal knee joint arthroplasty infection (Bernthal et al, 2010;Berretta et al, 2017;Kaur et al, 2016;Niska et al, 2012;Stavrakis et al, 2016;Thompson et al, 2017;Young et al, 2015). In these models, the inoculation strategy generally consists of directly injecting 10 2 -10 4 CFU of S. aureus into the joint space after that an orthopaedic hardware, typically a k-wire, has been implanted in a retrograde fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common mouse models are periprosthetic models of infection, which are employed to investigate the efficacy of different treatment modalities in a posttotal knee joint arthroplasty infection (Bernthal et al, 2010;Berretta et al, 2017;Kaur et al, 2016;Niska et al, 2012;Stavrakis et al, 2016;Thompson et al, 2017;Young et al, 2015). In these models, the inoculation strategy generally consists of directly injecting 10 2 -10 4 CFU of S. aureus into the joint space after that an orthopaedic hardware, typically a k-wire, has been implanted in a retrograde fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm eradication requires an increased antibiotic concentration, up to 1000 times more than planktonic cells (Olson et al, 2002), and most standard-of-care antibiotics (e.g. vancomycin and gentamicin) are ineffective against bacteria in biofilms (Sanchez et al, 2015;van de Belt et al, 2000). Consequently, implant retention during staged revision surgery of established infections results in a 57 % treatment failure rate (Lee et al, 2010;Marculescu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…By using both in vivo BLI and ex vivo CFU enumeration, we found that all of the monotherapy antibiotics reduced but did not clear the bacterial infection, whereas the combinatorial antibiotics with rifampin eliminated the infection in almost all of the mice . Notably, the oral‐only combinatorial therapy of linezolid plus rifampin was equally effective as combinatorial parenteral antibiotics plus rifampin, suggesting that such this alternative could be an option in humans to avoid the need for long‐term central venous access . However, in a spine OIAI model, Hu et al used in vivo BLI to evaluate 2 weeks of treatment with vancomycin alone or in combination with rifampin, and neither resulted in bacterial clearance as the infection rebounded soon after the antibiotic therapy was stopped …”
Section: Treatmentmentioning
confidence: 98%
“…We found that tigecycline and daptomycin had a broader effective dose range than vancomycin in preventing the MSSA and MRSA OIAI . Regarding antibiotic treatments of an OIAI, we used our K‐wire mouse model of S. aureus OIAI in which the bacteria (Xen36 or SAP231) was inoculated at the time of surgical implant placement, and following a 1‐ or 2‐week incubation period, systemic therapy was initiated for 6 total weeks with monotherapy antibiotics (e.g., vancomycin, daptomycin, linezolid, doxycycline, or ceftaroline at human exposure doses) or combinatorial antibiotic therapy of a subset of these antibiotics (vancomycin, daptomycin, linezolid, and ceftaroline) plus oral rifampin . By using both in vivo BLI and ex vivo CFU enumeration, we found that all of the monotherapy antibiotics reduced but did not clear the bacterial infection, whereas the combinatorial antibiotics with rifampin eliminated the infection in almost all of the mice .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation